Fifty playwrights on their craft - Jester, Caroline; Svich, Caridad (Bloomsbury Publishing series., 2018)
"In a series of interviews with fifty playwrights from the US and UK, this book offers a fascinating study of the voices, thoughts, and opinions of today's most important dramatists"